Analisis Penggunaan Metode Jarimatika untuk Meningkatkan Perkalian di Sekolah Dasar - Erica Anyelir; Eza Pratama Aulia Putri; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to evaluate the effectiveness of the Jarimatika method in enhancing elementary school students’ multiplication skills. The research stems from the issue of students’ limited understanding of multiplication concepts, often caused by monotonous and less engaging teaching methods. A literature review approach was employed by examining eight relevant previous studies. Data analysis was conducted by comparing findings across various sources. The results indicate that the Jarimatika method significantly improves student learning outcomes, both in terms of average scores and mastery levels. Moreover, it boosts students’ motivation and active participation during the learning process, proving effective across different grade levels. The use of fingers as a counting tool helps make the learning experience more tangible, enjoyable, and accessible for students. Therefore, Jarimatika is recommended as a viable alternative strategy for teachers in teaching mathematics at the elementary level, especially for multiplication topics.